Stories in Relationship: Experience, Identity, and Curriculum Making in an Elementary Classroom - Murphy, M. Shaun (LEARNing Landscapes, 2009)
In this paper the narratives of one teacher and two children show how nested knowing, relational knowing based on personal epistemologies, shaped a narrative understanding of experience and curriculum making in an elementary classroom. Issues of interruptions, ethical tensions, shifts in relationship, and subsequent shifts in knowing are explored. The nested nature of knowing was not only central to the relationship of the teacher and the children, but was also part of the relationships among the children.